Investigation on the performance of dedicated radiotherapy positioning devices for MR scanning for prostate planning. (8th March 2015) - Sun, Jidi; Dowling, Jason A.; Pichler, Peter; Parker, Joel; Martin, Jarad; Stanwell, Peter; Arm, Jameen; Menk, Fred; Greer, Peter B.
Abstract : The purpose of this study was to investigate performance of the couch and coil mounts designed for MR‐simulation prostate scanning using data from ten volunteers. Volunteers were scanned using the standard MR scanning protocol with the MR coil directly strapped on the external body and the volunteer lying on the original scanner table. They also were scanned using a MR‐simulation table top and pelvic coil mounts. MR images from both setups were compared in terms of body contour variation and image quality effects within particular organs of interest. Six‐field conformal plans were generated on the two images with assigned bulk density for dose calculation. With the MR‐simulation devices, the anterior skin deformation was reduced by up to 1.7 cm. The hard tabletop minimizes the posterior body deformation which can be up to 2.3 cm on the standard table, depending on the weight of volunteer. The image signal‐to‐noise ratio reduced by 14% and 25% on large field of view (FOV) and small FOV images, respectively, after using the coil mount; the prostate volume contoured on two images showed difference of 1.05 ± 0.66 cm 3 . The external body deformation caused a mean dose reduction of 0.6 ± 0.3 Gy, while the coverage reduced by 22 % ± 13 % and 27 % ± 6 % in V 98 and V 100, respectively. A dedicated MR simulation setup for prostate radiotherapy is essential to ensure the agreement between planning anatomy and treatment anatomy. The image signal was reduced after applying the coil mount, but no significant effect was found on prostate contouring. PACS numbers: 87.55.D‐, 87.61.‐c, 87.57.C‐